2022
DOI: 10.21608/pssjn.2022.120647.1176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Safety Program for Nurses on Medication Administration

Abstract: Background: Patients' safety is the main concern of all health-care systems around the world; one of international patient safety goal is medication administration safety aim: determine the effect of patient safety training program for nurses on medication administration at Damanhour Chest Hospital. Used for applying this study subjects and method: Design: Quasi-experimental design. Setting: study was carried out at critical care unit in Damanhour Chest Hospital. Subjects: Sample of the study staff nurses work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…In addition, the current study illustrated a correlation between the total studied nurses' knowledge and their total patients' safety, which was statistically significant (P= < 0.05). this result agreed with (Abu Hussein, et al, 2022) in the study entitled "Effect of Patient Safety Program for Nurses on Medication Administration" which showed that significance was found between patient safety attitude and medication administration knowledge. The researcher's opinion when nurses have the knowledge, they prevent errors and enhance patients' safety.…”
Section: Table (3) Frequency and Percentage Distribution Of The Nurse...supporting
confidence: 89%
“…In addition, the current study illustrated a correlation between the total studied nurses' knowledge and their total patients' safety, which was statistically significant (P= < 0.05). this result agreed with (Abu Hussein, et al, 2022) in the study entitled "Effect of Patient Safety Program for Nurses on Medication Administration" which showed that significance was found between patient safety attitude and medication administration knowledge. The researcher's opinion when nurses have the knowledge, they prevent errors and enhance patients' safety.…”
Section: Table (3) Frequency and Percentage Distribution Of The Nurse...supporting
confidence: 89%